1983
DOI: 10.1093/bja/55.4.349
|View full text |Cite
|
Sign up to set email alerts
|

Ro 15–1788 Antagonizes the Effects of Diazepam in Man Without Affecting Its Bioavailability

Abstract: In a double-blind, placebo-controlled three-way cross over study, the efficacy of Ro 15-1788 200 mg, a new benzodiazepine antagonist, in blocking the amnesic, cognitive, psychomotor and subjective effects of diazepam 20 mg, was investigated in a group of six healthy male volunteers. The amnesic effects of diazepam were markedly attenuated by the combined administration of Ro 15-1788. The psychomotor and subjective effects of diazepam by mouth were most pronounced 2.5 h after administration. Concurrent oral adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…Work on human subjects has shown that Ro 15-1788 is able to block the predicted effects of benzodiazepines whether given prior to (Gath et al 1984), simultaneously with (Ismail et al 1981;Gaillard and Blois 1983;Darragh et al 1981Darragh et al , 1982aO'Boyle et al 1983) or subsequent to benzodiazepine administration (Ismail etal. 198l;Ziegler and Schalch 1982;Laurian et al 1984).…”
mentioning
confidence: 99%
“…Work on human subjects has shown that Ro 15-1788 is able to block the predicted effects of benzodiazepines whether given prior to (Gath et al 1984), simultaneously with (Ismail et al 1981;Gaillard and Blois 1983;Darragh et al 1981Darragh et al , 1982aO'Boyle et al 1983) or subsequent to benzodiazepine administration (Ismail etal. 198l;Ziegler and Schalch 1982;Laurian et al 1984).…”
mentioning
confidence: 99%
“…The present findings, combined with previous evidence that flumazenil blocks or reverses CDP-induced impairment of successive discrimination [Cole, 1989a1, suggest that mediation mechanisms of the BDZ drug class may also share common properties. Additional evidence that flumazenil partially blocks or reverses BDZinduced impairment of learning in tasks markedly different from the present one [Bonetti et al, 1982;O'Boyle et al, 1983;Thiebot et al, 19831 suggests that central BDZ receptors may play an even more generalized (but not necessarily exclusive) role in mediating drug-induced impairment.…”
Section: Discussionmentioning
confidence: 53%
“…1977;Snyder el al.. 1977;Wolkowitz and Tinklenberg, 1985;Wolkowitz et al, 1985c], The BZD recep tor (which is functionally linked to the GABA receptor, cf. Paul et al [1981], Wolkowitz and Paul [1985]) is directly implicated in these effects since Ro 15-1788, a BZD receptor antagonist without intrinsic activity, blocks the BZD-induced amnesia [O'Boyle et al, 1983]. Many studies implicate the encoding or consolidation phase of memory processing rather than initial registra tion or subsequent retrieval, as being vulnerable to the BZD's disruptive effects [Ghoneim and Mewaldt, 1975;Frumin et al, 1976].…”
Section: Catecholaminesmentioning
confidence: 99%